2012
DOI: 10.17221/347/2011-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various rootstocks on the yield and grape composition of Sauvignon Blanc

Abstract: This influence of various rootstocks on the yield and grape composition of Sauvignon Blanc was examined. The yield on rootstock 41B/72 was 1 kg/vine or more higher than on rootstocks SO4 cl. 31, Riparia cl. 1 and Kober 5BB. The vines grafted on the Börner rootstock gave the highest weight of 100 berries (241 g). The highest seed weight of 100 berries (6.9 g) was found on rootstock 196/17 Cl, while the lowest one was on the Riparia cl. 1 (5.6 g). There was a strong, positive correlation (r = 0.91) between the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Rootstocks had no significant effects on yields (Table 1). In previous studies, there were no consistent conclusions for the influence of rootstocks on yields [1,2,3,5,6,15,16,23]. Rootstocks can give rise to different reactions to yield formation in different types of soil, and it was reported that yields of different grafted vines only significantly differed in shale soil when compared to granite soil [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rootstocks had no significant effects on yields (Table 1). In previous studies, there were no consistent conclusions for the influence of rootstocks on yields [1,2,3,5,6,15,16,23]. Rootstocks can give rise to different reactions to yield formation in different types of soil, and it was reported that yields of different grafted vines only significantly differed in shale soil when compared to granite soil [13].…”
Section: Resultsmentioning
confidence: 99%
“…Juice titratable acidity and pH were not affected by either rootstock or season in this study (Table 2). There have been no agreed conclusions about the influence of rootstocks on titratable acidity and pH in previous studies [2,5,10,16,17,19,20,22,26,27]. Since potassium can precipitate tartrates in juice, leading to the reduction of tartaric acid, potassium in juice determines the titratable acidity and pH to a great extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rootstock effects on vine yield and winegrape composition have been widely evaluated since the introduction of rootstocks at the end of the 19th century, under a broad range of soil and climatic conditions for all major cultivars [aggregated information can be found, for instance in May (1994), Cordeau (1998), Fregoni (1998), Galet and Smith (1998), Hidalgo (1999), Morris et al (2007), Pulko et al (2012), Miele and Rizzon (2017) and Marín et al (2019)]. Nevertheless, considering that the performance of scions grafted to different rootstocks is not consistent, as scion × rootstock interactions occur (Clingeleffer et al 2019), and that site‐specific effects can be observed because of variation in climate and soil (Walker et al 2019), it is necessary to specifically evaluate each scion cultivar and growing conditions.…”
Section: Challenges Related To Conferred Vigour Yield and Grape Compmentioning
confidence: 99%
“…When speaking about rootstocks, this effect is dependent on the ratio existing between the leaf area of the plant and its yield. The balanced uptake of nutrients and water as well as the re-distribution of individual elements within the grapevine plant are closely related to changes in the phenology of plants and it is well known that these processes are significantly influenced by rootstocks (Pulko et al 2012). Resistance to yearly different conditions will be paid great attention with respect to the balanced quality of grapes.…”
mentioning
confidence: 99%